Development of interactive learning media based on augmented reality in the material of Indonesian regional map - Nakwah Salsabila Rantika; Lativa Qurrotaini (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2026)
The existing problem is how to develop interactive learning media based on Augmented Reality in the material of the Indonesian Regional Map so that it is valid. In this application there are Info features, AR Objects, Teaching Modules, Materials, Quizzes, and Profile Developer. The method used is Research and Development (RnD) with the ADDIE Development Model (Analyze, Design, Development, Implementation, and Evaluation). This research was conducted at MIN 19 JAKARTA with research subjects of class 5C students. The results of the study showed that the developed learning media was very valid based on the assessment of material experts with a percentage of 95%, the assessment of media experts with a percentage of 94.5%, and the assessment of language experts with a percentage of 95%. Small Group Test 1 with a percentage of 89%, Small Group Test 2 with a percentage of 95%, and Large Group Test with a percentage of 90.95% all showed very valid results. The effectiveness of the media was measured using N-Gain. The Small Group Test 1 score was 76.85%, with a Valid score. The Small Group Trial 2 score was 81%, and the Large Group Trial score was 80.45%. Teacher responses were 78%, with a Valid score, and Student responses were 87%, with a Valid score. The Learning Success Test also showed valid results with a score of 85.47%.